Higher National Diploma Students Perception of Entrepreneurship Development Course: Evidence from Tamale Polytechnic - Kere, Daud Osman; Awunyo-Vitor, Dadson (Journal of Asian Business Strategy, 2012)
The study examined Higher National Diploma (HND) students’ perception of the entrepreneurship development course in Tamale Polytechnic. Data for the study were obtained from HND students from four schools within Tamale Polytechnic namely School of Business, School of Engineering and School of Applied Sciences.Data was analysed using Statistical Package for Social Scientist (SPSS).The study revealed that, facilities for teaching and learning of entrepreneurship were inadequate except lecture halls and furniture. Generally, the respondents perceive instructional strategiesand assessment techniques to be ineffective. Similarly the findings suggest that, the recommended teaching and learning methods as well as the assessment techniques were not effectively utilized, as teaching tends to be more theoretical. The study concludes by suggesting that the provision of adequate resources is very necessary to effective teaching and learning the Entrepreneurship Development Course.